Diversity-oriented synthesis : basics and applications in organic synthesis, drug discovery, and chemical biology - Trabocchi, Andrea, Ed (Wiley, 2013)
"This book overviews diversity-oriented synthesis (DOS), one of the leading and dynamic topics in organic chemistry and drug discovery"--